Nomenclatural priority of the genus Linochilus over Piofontia (Asteraceae: Astereae) - Saldivia, Patricio; Vargas, Oscar M.; Orlovich, David A.; Lord, Janice M. (Phytotaxa, 2019)
Linochilus Bentham (1845) has priority as the correct name for the recently reinstated genus Piofontia Cuatrecasas (1943) segregated from Diplostephium Kunth (1820). A brief taxonomic historical account is provided in order to explain the taxonomic problem. A list of 61 names within Linochilus is given, including 59 new combinations. The 60 combinations recently created for Piofontia are listed as synonyms.